Comparative Proteomic Analysis Reveals New Insights Into the Common and Specific Metabolic Regulation of the Diatom Skeletonema dohrnii to the Silicate and Temperature Availability - Thangaraj, Satheeswaran; Giordano, Mario; Sun, Jun (Frontiers in Plant Science, 2020)
Silicate (Si) and temperature are essential drivers for diatom growth and development in the ocean. Response of diatoms to these particular stress has been investigated; however, their common and specific responses to regulate intracellular development and growth are not known. Here, we investigated the combination of physiological characteristics and comparative proteomics of the diatom Skeletonema dohrnii grown in silicate- and temperature-limited conditions. Results show that cell carbon and lipid quotas were higher at lower-temperature cells, whereas cellular phosphate was higher in cells grown with lower Si. In silicate-limited cells, nitrate transporters were downregulated and resulted in lower nitrate assimilation, whereas the phosphate transporters and its assimilation were reduced in lower-temperature conditions. In photosynthesis, lower silicate caused impact in the linear electron flow and NADPH production, whereas cycling electron transport and ATP production were affected by the lower temperature. Concerning cell cycle, imbalances in the translation process were observed in lower-silicate cells, whereas impact in the transcription mechanism was observed in lower-temperature cells. However, proteins associated with carbon fixation and photorespiration were downregulated in both stress conditions, while the carbohydrate and lipid synthesis proteins were upregulated. Our results showed new insights into the common and specific responses on the proteome and physiology of S. dohrnii to silicate and temperature limitation, providing particular nutrient (Si)- and temperature-dependent mechanisms in diatoms.